Mechanical Properties of Bump-Prone Coal with Different Porosities and Its Acoustic Emission-Charge Induction Characteristics under Uniaxial Compression - Xin Ding; Xiaochun Xiao; Xiangfeng Lv; Di Wu; Jun Xu (Advances in Civil Engineering)
Discreteness of mechanical property affected by the intimal damage, which emerged with various degrees of material composition and geological structure, is the difference in porosity macroscopically. Although various porosities directly affect fracture activity, damage evolution and mechanical behaviour of coal bring on the bump-prone assessment error, and disaster happened “ahead of time” in deep underground energy source exploration, little research to date has focused on them. In this paper, the mechanical properties of bump-prone coal samples with different porosities were studied by uniaxial compression test and the initial damage caused by gangue and organic fracture in coal observed by CT. The result indicated that the evolution of coal strength and the logarithm of porosity were expressed by a linear negative correlation and the elastic modules decreased with the initial damage increased. A new quantitative description of damage variables is established by theoretical derivation to reflect the process of cracks formation and expiation in coal, based on volumetric strain and initial porosity. According to the Mohr–Coulomb principle, the effective stress of coal sample with higher the porosity is more likely to reach the shear strength and destruction. The amplitudes and accumulation of AE energy and charge pulse indeed vary with the stress loading stages and strength. The frequency of AE waveform is dominated in three bands (1∼50 kHz, 100∼150 kHz, and 175∼200 kHz) and that of charge induction had one frequency band 1∼100 Hz, and the amplitudes of time domain and main frequency components increased with stress improved. Both of them originated from cracks and belong to homologous signals, crack development bound to be accompanied by stress wavelet, not necessarily free charge; meanwhile, charge pulse being emerged means there must be cracks interaction and the acoustic emission signals are generated prior to charge induction.